2019
DOI: 10.1021/acs.biomac.9b00769
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Shape-Holding Collagen Hydrogel for Cell Encapsulation and Delivery Cross-linked Using Thiol-Michael Addition Click Reaction

Abstract: Injectable hydrogels based on extracellular matrix-derived polymers show much promise in the field of tissue engineering and regenerative medicine. However, the hydrogels reported to date have at least one characteristic that limits their potential for clinical use, such as excessive swelling, complicated and potentially toxic cross-linking process, or lack of shear thinning and self-healing properties. We hypothesized that a collagen hydrogel cross-linked using thiol-Michael addition click reaction would be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 68 publications
3
64
0
Order By: Relevance
“…These results, obtained using human cells, are as good as the results of studies which reported the great biocompatible hydrogels. [13,37] In this regard, our findings demonstrated that the hydrogel of this study is highly biocompatible in cell culture and expansion studies.…”
Section: Live/dead and Mtt Assaysupporting
confidence: 57%
“…These results, obtained using human cells, are as good as the results of studies which reported the great biocompatible hydrogels. [13,37] In this regard, our findings demonstrated that the hydrogel of this study is highly biocompatible in cell culture and expansion studies.…”
Section: Live/dead and Mtt Assaysupporting
confidence: 57%
“…In a series work from the laboratory of Wang, thiolated‐hyaluronic acid was crosslinked with different hyperbranched polymers containing residue acrylate moieties via this thiol‐Michael addition, yielding hydrogels with promising applications in wound healing [ 120,239 ] and cartilage tissue engineering [ 240 ] after encapsulating cells. Various polymers including collagen, [ 124 ] hyaluronic acid, [ 241 ] dextran, [ 121 ] chondroitin sulfate, [ 122 ] were crosslinked by this chemistry and used for cell culture. This chemistry has also led to the FDA approved product—Premvia (K134037), which is crosslinked from three compounds: thiol–modified hyaluronan, thiol–modified gelatin, and PEG diacrylate.…”
Section: Crosslinking Chemistrymentioning
confidence: 99%
“…That allowed for the formation of injectable hydrogels with shear-thinning and self-healing properties because of the low degree of thiol modification on collagen and the formation of an interhelical assembly. [82] Similarly, Wang et al described the synthesis of an injectable hydrogel made from thiolate-modified hyaluronic acid and quinonemodified polydopamine. When injected into heart muscle, this hydrogel was found to improve cardiac functions by decreasing inflammation.…”
Section: Chemically Crosslinked Injectable Hydrogelsmentioning
confidence: 99%